Identification of hydroxytyrosyl oleate, a derivative of hydroxytyrosol with anti-inflammatory properties, in olive oil by-products. (1st May 2019) - Plastina, Pierluigi; Benincasa, Cinzia; Perri, Enzo; Fazio, Alessia; Augimeri, Giuseppina; Poland, Mieke; Witkamp, Renger; Meijerink, Jocelijn
Highlights: Anti-inflammatory potential of hydroxytyrosyl esters was studied in RAW264.7 cells. Hydroxytyrosyl oleate decreased nitric oxide and prostaglandin E2 production. The inhibitory effect was observed also at a transcriptional level. Hydroxytyrosyl oleate was identified for the first time in olive oil by-products. Hydroxytyrosyl oleate is a significant form in which hydroxytyrosol occurs. Abstract: Hydroxytyrosyl esters with short, medium and long acyl chains were evaluated for their ability to reduce nitric oxide (NO) production by lipopolysaccharide-stimulated RAW264.7 macrophages. Among the compounds tested, C18 esters, namely hydroxytyrosyl stearate (HtySte) and hydroxytyrosyl oleate (HtyOle), were found to decrease NO production in a concentration-dependent manner, while the other compounds, including the parent hydroxytyrosol, were ineffective in the tested concentration range (0.5–5 μM). Further study of the potential immune-modulating properties of HtyOle revealed a significant and concentration-dependent suppression of prostaglandin E2 production. At a transcriptional level, HtyOle inhibited the expression of inducible NO synthase, cyclooxygenase-2 and interleukin-1β. Moreover, HtyOle was identified for the first time in olive oil by-products by means of high performance liquid chromatography coupled with mass spectrometry. By contrast, HtyOle was not found in intact olives. Our results suggest that HtyOle is formed during oil processing and represents a significant form in which hydroxytyrosol occurs.